Особливості застосування замінників неорганічних фосфатів у технології виробництва м’ясопродуктів - Страшинський, Ігор Мирославович; Грицай, Максим Сергійович (My University, 2023)
В оглядовій статті визначено, що м’ясопродукти, які містять натуральні інгредієнти, в майбутньому можуть стати пріоритетним вибором у структурі харчування населення. Наведено природні замінники фосфатів та обфунтовано можливості використання інгредієнтів рослинного походження (крохмаль, волокна або насіння); грибних інгредієнтів (гриби та грибні екстракти); інгредієнтів з водоростей; інгредієнтів тваринного походження (неорганічні сполуки з морепродуктів або курячих яєць). Визначено особливості їх застосування з огляду на зміну функціонально- технологічних властивостей м’ясних і м’ясомістких систем, органолептичних характеристик і терміну зберігання. Окреслено основні проблеми щодо використання натуральних інгредієнтів у порівнянні з неорганічними фосфатами.

It is proved that the use of food phosphates for the production of meat products has a positive effect on muscle proteins, contributing to a decrease in the growth of microflora, color stability and oxidative processes in meat products. In addition, by increasing the moisture-binding and emulsifying ability of meat, phosphate preparations allow to stabilize the pH of meat and meat-intensive minced meat, improve its consistency and in - crease the yield of finished products. The necessity of developing food products of a new generation with a high protein content has been substantiated. It is determined that meat products containing natural ingredients in the future may become a priority choice in the structure of population nutrition. It is proved that at the time there is a need to replace inorganic phosphates used in meat products technology with organic food additives that reduce the risk of a number of diseases, as well as due to changes in consumer preferences regarding the presence of a "clean label" on the packaging of products. Alternatively, the use of natural ingredients is considered. Natural substitutes for phosphates are given and possibilities of using ingredients of plant origin (starch, fiber or seeds) are substantiated; mushroom ingredients (mushrooms and mushroom extracts); ingredients from algae; ingredients of animal origin (inorganic compounds from seafood or chicken eggs). The features of their application in view of the change in the functional and technological properties of meat and meat-in- tensive systems, organoleptic characteristics and shelf life are determined. The main limiting factors for the removal of inorganic phosphates fromprocessed meat products were noted. The main prob - lems regarding the use of natural ingredients in relation to inorganic phosphates are outlined. Attention is focused on the possibility of increasing the cost of products using natural ingredients and the need to ensure sustainable production costs at processing enterprises.
Keywords: кафедра технології м’яса і м’ясних продуктів; рецептура; функціональні властивості; безпечність; неорганічні фосфати; meat system; formulation; functional properties; safety; inorganic phosphates